Cation-modified biochars to remove phosphate from aqueous solution and their agronomic value - Nardis, Bárbara Olinda (2020)
Phosphorus (P) recovery from waste and wastewater is a growing need in the current and future scenarios. The emergence of adsorbents such as cation-modified biochar is a technology that can be used from different feedstocks. The objectives of this work were: i) to study different biomasses impregnated with magnesium (Mg2+) to recover P from aqueous solution and its potential as a fertilizer; ii) to evaluate the impregnation with different cations (Mg2+, Fe3+ and Al3+) and production pyrolysis condition (muffle furnace and vertical furnace with N2 flow) in the adsorption of P and physical and chemical characteristics of the biochars; and iii) to evaluate the speciation of P adsorbed in the cation-modified biochar, using X-ray absorption spectroscopy (XANES). In the first study, biochars were produced by slow pyrolysis at 500 °C from poultry litter (PLB), pig manure (PMB) and sewage sludge (SSB), impregnated with ± 10% magnesium Mg2+ in the biochar. They were characterized and their adsorption capacity studied. Subsequently, the efficiency of biochars in retaining and releasing P was evaluated. The main results show that PMB and PLB impregnated with Mg and loaded with P had the potential to be reused as phosphate fertilizers; their efficiencies were equal to or greater than TSP in the short-term cultivation of maize, in addition to improving soil fertility for other cropping cycles. In another study, pig manure was impregnated with ± 20% Mg2+, aluminum (Al3+) and iron (Fe3+) and produced under two pyrolysis condition of preparation (muffle furnace and vertical furnace under N2 flow). A detailed physical-chemical characterization was carried out and a study was made of the adsorption and release capacity of P from aqueous solution. PMB impregnated with 20% Mg and produced in a muffle furnace showed the highest adsorption of P (231 mg g-1, SIPS isotherm) when compared to materials impregnated with Al and Fe. The biochar modified with Fe showed the lowest adsorption capacity of P not allowing the modeling of adsorption. The pyrolysis condition (muffle - low O2 or furnace under N2) had no significant influence on the characteristics that govern adsorption, such as functional groups, surface area, quantity and size of pores and formation of minerals. Finally, in another study the biochars modified with cations and loaded with P were analyzed by X-ray absorption near edge structure (XANES). The study indicated that in biochar not impregnated with cations, calcium phosphates (P-Ca) were the main chemical species, with a predominance of hydroxyapatite. In the biochar impregnated with Al, there was a predominance of P-Al compounds and the same was observed for Fe, that is, the species of P-Fe predominated. On the other hand, for the biochar impregnated with Mg, P-Mg species were identified, but the P-Ca species predominated due to the amount of Ca in the pig manure and the trend of precipitation of the P-Ca compounds over P-Mg compounds. The biochar modified with Mg is more recommended for tertiary treatment to remove P in sewage treatment plants, due to its high P adsorption capacity and performance potential as a phosphate fertilizer superior to conventional soluble sources.